2003
DOI: 10.1088/0953-8984/15/6/319
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport properties of flux melt grown single crystals of Co-substituted manganites with perovskite structure

Abstract: Single crystals of La1−xBaxMn1−yCoyO3 (0.26 ≤ x ≤ 0.37; 0 ≤ y ≤ 0.31) perovskites were grown by the flux melt technique using the BaO–B2O3–BaF2 ternary system as a solvent. It was found that the cobalt content in the crystals is determined by the average oxidized state of the manganese ions and depends nonlinearly on the molar ratio of Co/Mn in the initial mixture. All the crystals exhibit ferromagnetic behaviour at low temperatures as well as a jump of resistivity and a magnetoresistance peak around the Curie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Such a temperature variation of magnetic susceptibility is characteristic for solids with antiferromagnetic ordering of the gadolinium and manganese sublattices. This observation is consistent with a magnetic structure reported for the Gd 0.67 Ca 0.33 MnO 3 [5][6][7].…”
Section: Magnetic Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Such a temperature variation of magnetic susceptibility is characteristic for solids with antiferromagnetic ordering of the gadolinium and manganese sublattices. This observation is consistent with a magnetic structure reported for the Gd 0.67 Ca 0.33 MnO 3 [5][6][7].…”
Section: Magnetic Resultssupporting
confidence: 92%
“…A strong role in magnetization reduction, played by a substitution of Gd ions onto the La sites, is also found both in magnitude and temperature variation of magnetization measured in static magnetic fields up to 6 T [5]. It is observed that the magnetization magnitude and the Curie temperature are monotonically suppressed when the Gd content x varies from 0 to 0.75.…”
Section: Magnetic Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…7 for the zero and 8 T cases. One may see that the phonon conductivity is overwhelming in the manganite studied, which is typically observed in manganites and cobaltites [3,14]. It is worth noticing that the electron/polaron contribution considerably increases especially below 140 K, when passing from zero to 8 T magnetic field.…”
Section: Article In Pressmentioning
confidence: 74%
“…The ortho rho mbic sym metry was found for the space gro up and l atti ce pa ra meters nm , nm , nm . The (La Ba Mn Co O sing le crysta l gro wn fro m Ûux mel t [24] was chara cteri zed by a pseudo-cubi c crysta l structure ( 0 390 nm ) wi th sm all rho mb ohedra l di storti on (space gro up ) at 300 K. The singl e crysta l of (La Ca Co O wa s gro wn by a Ûoati ng zone techni que and was chara cteri zed by tri gona l sym metry (space gro up wi th l atti ce consta nts nm , nm i n hexag onal system setti ng s). Twi nni ng structure sim i lar to tha t i n La Sr Co O [20] wa s observed i n the i nvesti gated (La Ca )Co O sam pl e.…”
Section: Introductionmentioning
confidence: 99%